Chitosan Membrane Embedded With ZnO/CuO Nanocomposites for the Photodegradation of Fast Green Dye Under Artificial and Solar Irradiation. Issue 13 (20th March 2018) - Alzahrani, Eman
Fast Green (FCF) dye is commonly used in both cytology and histology applications. Previous studies have found that it can cause mutagenic and tumorigenic effects in experimental human and animal populations. It can also be a source of skin, eye, respiratory, and digestive irritation. The purpose of this study was to examine the use of thin film membranes to degrade FCF. A thin film membrane of chitosan (CS) was fabricated and subsequently filled with zinc oxide nanoparticles (ZnO) or ZnO/CuO-heterostructured nanocomposites. The CS membrane was used as a matrix, and the nanomaterials were used as photocatalysts. The prepared membranes were characterised by four analytical techniques: atomic force microscopy, scanning electron microscopy, X-ray diffraction, and energy-dispersive X-ray analyses. The photocatalytic activity of the fabricated membranes was evaluated by performing experiments in which aqueous solutions of FCF dye that contained the fabricated membrane were irradiated with solar light or UV light. The photodegradation percentage was spectrophotometrically determined by monitoring the maximum wavelengths (λmax ) of FCF at 623 nm for different irradiation times. The decolourisation percentages of the dye under solar light were 57.90% and 60.23% using the CS-ZnO and CS-ZnO/CuO membranes, respectively. When UV light irradiation was employed as the source of irradiation, the photodegradation percentages of FCF were 71.45% and 91.21% using the CS-ZnO and CS-ZnO/CuO membranes, respectively. These results indicated that the best photocatalytic system for the degradation of FCF dye was CS-ZnO/CuO membrane in combination with UV light irradiation. The study also found that it was easy to separate the prepared membranes after the reaction without the need for a centrifuge or magnet. The results demonstrate the potential for CS-ZnO and CS-ZnO/CuO membranes for use as effective sorbents during the process of photodegradation of harmful dyes within waste water recycling practices.